2008
DOI: 10.2495/eeia080121
|View full text |Cite
|
Sign up to set email alerts
|

Beach users’ aesthetic and economic evaluation of a “minor change” to the hard engineering coastal defences at Wiseman’s Bridge, Pembrokeshire, Wales

Abstract: This study evaluated the visual impact of the new hard engineering coastal defences at Wiseman's Bridge, Pembrokeshire, Wales. This beach had existing hard coastal defences, road, car park and dwellings, which may have lead planners' to believe that the change would not impact upon beach users' enjoyment.However, a change in coastal scenery was expressed by 79% of those surveyed, using the perceptual approach, whilst the beach classification was unaffected using two checklist models. The beach is primarily uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…However, it is important to stress that both interventions are preferred to the donothing approach. In the literature (Blakemore et al 2008;Phillips and Jones 2006;Roca et al 2008) and in interviews with academics and experts, it is recognized that light interventions can act as effective short-term measures, in the area of influence of the intervention, but in the long term are characterized by vulnerabilities that affect the direct and adjacent areas of influence. Moreover, generally, heavy engineering is more expensive than alternative light intervention techniques, which are a more natural method.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to stress that both interventions are preferred to the donothing approach. In the literature (Blakemore et al 2008;Phillips and Jones 2006;Roca et al 2008) and in interviews with academics and experts, it is recognized that light interventions can act as effective short-term measures, in the area of influence of the intervention, but in the long term are characterized by vulnerabilities that affect the direct and adjacent areas of influence. Moreover, generally, heavy engineering is more expensive than alternative light intervention techniques, which are a more natural method.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Moreover, generally, heavy engineering is more expensive than alternative light intervention techniques, which are a more natural method. Blakemore et al's (2008) 2017) also concluded that some individuals have negative attitudes toward preferences for seawalls to protect properties. The willingness to pay for coastal zone interventions evidenced in our study is consistent with empirical studies over coastal zone preservation.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…to their total economic value. Beaches and coastal areas have been the subject of greater research effort, and further examples of published valuations for these areas includeBlakemore et al (2008),Christie and Gibbons (2011),King (1995),Polyzos and Minetos (2007),Ropars-Collet et al (2015),Voke et al (2013), andWhitmarsh et al (1999). Elicitation of the values held by scuba divers for subtidal habitats has shown that rocky and sedimentary areas have different values(Jobstvogt et al 2014), …”
mentioning
confidence: 99%